River Water Quality Status Based on Variation in Family Biotic Index in Jilu River Malang City - East Java: Status Kualitas Air Sungai Berdasarkan Variasi Famili Biotik Indeks di Sungai Jilu Kota Malang – Jawa Timur - Vikriansyah, Muchammad Faruq; Prasetyo, Hamdani Dwi; Latuconsina, Husain (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2025)
Biological indicators utilize animals as markers to assess water quality in specific water bodies. Among various bioindicators, benthos is widely used for evaluating river water quality due to its sensitivity to environmental changes and its tendency to remain in specific areas. This study aimed to determine the water quality status of the Jilu River. Sampling was conducted using a purposive sampling method, with macroinvertebrates collected using a grab sampler to extract sediment from the riverbed. The sediment was then sieved to isolate benthic organisms from five locations with varying characteristics: industrial area, rice fields, natural riparian zone, residential area, and educational tourism park. The Family Biotic Index (FBI) was used to analyze the benthic macroinvertebrates, identifying 11 families: Thiaridae, Tubificidae, Chironomidae, Viviparidae, Simuliidae, Philopotamidae, Baetidae, Heptageniidae, Gecarcinucoidea, Caenidae, and Coenagrionidae. The Thiaridae family dominated across all locations. Based on FBI analysis, water quality along the Jilu River ranged across three categories: good, moderate, and very poor. The findings highlight the need for effective management strategies to mitigate pollutant loads and preserve the river’s water quality.